Variation of Magnesium, One of the Macronutrients, in Some Trees Based on Organs and Species - Ramazan Erdem; İsmail Koç; Hatice Çobanoğlu; Hakan Şevik (Forestist)
Plants’ ability to perform the expected functions depends on their ability to grow and develop healthily. Environmental factors shape plant growth, and nutrients are one of the most main features a&ecting plant development. Magnesium, one of the macronutrients for plants, is necessary for plant growth and development. It is also one of the essential heavy metals, and it is critical to watch the change in its concentration in the air regarding human and environmental health. This study aimed to reach information about the change of magnesium concentration in some trees based on species and organs as well as its transfer after it is taken into the plant. In addition, it is aimed to observe the variation of magnesium contamination in the air and to determine the species that can be used to reduce pollution. For this purpose, log samples from Cedrus atlantica, Pinus pinaster, Picea orientalis, Cupressus arizonica, and Pseudotsuga menziesii trees were used. As a result, it has been shown that the transfer of magnesium concentration in the wood of the studied species is limited. While the highest magnesium accumulation was obtained in Cupressus arizonica species, the highest concentrations were obtained in the outer bark and the lowest in the inner bark as the plant organ. In addition, it has been determined that the magnesium concentration in the air is related to the tra'c density